Limited Effect of Dopaminergic Medication on Straight Walking and Turning in Early-to-Moderate Parkinson’s Disease during Single and Dual Tasking - Elshehabi, Morad; Maier, Katrin S.; Hasmann, Sandra E.; Nussbaum, Susanne; Herbst, Heinz; Heger, Tanja; Berg, Daniela; Hobert, Markus A.; Maetzler, Walter (Frontiers in Aging Neuroscience, 2016)
Background In Parkinson’s disease (PD), the effects of dopaminergic medication on straight walking and turning were mainly investigated under single tasking (ST) conditions. However, multitasking situations are considered more daily relevant. Methods Thirty-nine early-to-moderate PD patients performed the following standardized ST and dual tasks as fast as possible for 1 min during On- and Off-medication while wearing inertial sensors: straight walking and turning, checking boxes, and subtracting serial 7s. Quantitative gait parameters as well as velocity of the secondary tasks were analyzed. Results The following parameters improved significantly in On-medication during ST: gait velocity during straight walking (p = 0.03); step duration (p = 0.048) and peak velocity (p = 0.04) during turning; velocity of checking boxes during ST (p = 0.04) and DT (p = 0.04). Velocity of checking boxes was the only parameter that also improved during DT. Conclusion These results suggest that dopaminergic medication does not relevantly influence straight walking and turning in early-to-moderate PD during DT.